Who is out there? What are they doing? Application of metagenomics and metaproteomics to reveal soil functioning - Antonietta Mello (Italian Journal of Mycology, 2017)
In order to link microbial community composition to ecological processes happening in the brûlé, a metaproteomics analysis was applied to a brûlé previously characterized by metagenomics. The metagenomics data had showed a reduced fungal biodiversity, a dominance of Tuber melanosporum and a reduced presence both of ectomycorrhizal Basidiomycota and of bacteria belonged to Pseudomonas and Flavobacteriaceae inside the brûlé. By metaproteomics analysis, the identified proteins revealed which biological processes were more represented or only present in the brûlé, and, among them, processes related to multiple stresses were identified in herbaceous plants. This study demonstrates that combining the data of metagenomics and metaproteomics gives the opportunity to potentially reveal the functioning of any environment.